1993
DOI: 10.1083/jcb.123.3.653
|View full text |Cite
|
Sign up to set email alerts
|

Regulated tyrosine phosphorylation at the tips of growth cone filopodia.

Abstract: Abstract. Several types of evidence suggest that protein-tyrosine phosphorylation is important during the growth of neuronal processes, but few specific roles, or subcellular localizations suggestive of such roles, have been defined. We report here a localization of tyrosine-phosphorylated protein at the tips of growth cone filopodia. Immunocytochemistry using a rnAb to phosphorylated tyrosine residues revealed intense staining of the tips of most filopodia of Aplysia axons growing slowly on a polylysine subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
62
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(71 citation statements)
references
References 53 publications
9
62
0
Order By: Relevance
“…Several components of this tip complex have been identified, including Ena/vasodilator-stimulated phosphoprotein actin-binding proteins (Lanier et al, 1999;Svitkina et al, 2003), the motor proteins myosin X and IIIa (Berg et al, 2002;Les Erickson et al, 2003), and ␤1-integrins (Wu et al, 1996). In addition, Wu and Goldberg (1993) identified a robust enrichment of tyrosine-phosphorylated proteins at the tips of growth cone filopodia. Although initially thought to inhibit filopodial extension, these findings were inconsistent with pharmacological experiments indicating that tyrosine kinase activity promotes axon extension in vitro and in vivo (Gomez et al, 1996;Worley and Holt, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several components of this tip complex have been identified, including Ena/vasodilator-stimulated phosphoprotein actin-binding proteins (Lanier et al, 1999;Svitkina et al, 2003), the motor proteins myosin X and IIIa (Berg et al, 2002;Les Erickson et al, 2003), and ␤1-integrins (Wu et al, 1996). In addition, Wu and Goldberg (1993) identified a robust enrichment of tyrosine-phosphorylated proteins at the tips of growth cone filopodia. Although initially thought to inhibit filopodial extension, these findings were inconsistent with pharmacological experiments indicating that tyrosine kinase activity promotes axon extension in vitro and in vivo (Gomez et al, 1996;Worley and Holt, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Detailed analysis of three growth cones with a total of 43 filopodia that were immotile and PY negative before BDNF application indicated that 40 of these filopodia acquired prominent PY accumulations at their tips within 15 min of BDNF stimulation. Subsequently, 39 of the 40 filopodia began to exhibit cycles of protrusion and retraction typical of motile filopodia on PDL (Wu and Goldberg, 1993) (supplemental movies 3, 4, available at www.jneurosci.org as supplemental material). Although there was a high degree of variability in the delay to filopodial PY accumulation, even within filopodia on the same growth cone, in every case filopodia that became motile after BDNF stimulation did so only after the accumulation of PY at their tip (Fig.…”
Section: Regulation Of Filopodial Py By Axon Guidance Cuesmentioning
confidence: 99%
“…Bag cell neurons were stained for phosphotyrosine using an immunocytochemistry protocol adapted from Wu and Goldberg (1993) and White and Kaczmarek (1997). Neurons were plated in the center of small (20 -40 l) wax rings (made from dental wax, as above) affixed to tissue culture dishes.…”
Section: Methodsmentioning
confidence: 99%
“…Phosphotyrosine was detected immunocytochemically using a monoclonal mouse IgG that has been widely used to stain for phosphotyrosine, including in Aplysia neurons (Wu and Goldberg, 1993). Staining of neurons cultured for 1 d showed both a uniform, diffuse signal over the entire soma, as well as a brighter, more intense signal near the membrane edge (n ϭ 32) (Fig.…”
Section: Immunocytochemically Detected Phosphotyrosine Is Lower In Rementioning
confidence: 99%
“…These facts suggest that integrity of F-actin networks might be necessary for the stimulation of FAK Tyr(P). We therefore tested the impact of cytochalasin D, which disrupts the actin cytoskeleton [15], on the upregulation of FAK Tyr(P) by PKC activity. B103 cell cultures were pretreated with 1 ~tM cytochalasin D for 2 h and subsequently treated with 200 nM PDBu for 10 min.…”
Section: Piis0014-5793(96)00435-8mentioning
confidence: 99%